PERAN KEPALA KAMPUNG DALAM MENINGKATKAN PELAYANAN PUBLIK DI KAMPUNG INOFINA DISTRIK MOSKONA UTARA KABUPATEN TELUK BINTUNI - APOKI, METTU SALAK; ROMPAS, WELSON; KIYAI, BURHANUDDIN (JURNAL ADMINISTRASI PUBLIK, 2019)
The increase in public services in a village or village cannot be separated from the roleof the village head. The success of village development is inseparable from the role of the villagehead as the leader in the village. Therefore, the role of the village head is very important in manyaspects of Kampung community life, including public services.This research focuses on the role ofthe village head in improving public services with the location of the study in Inofina Village,North Moskona District, Teluk Bintuni Regency. The aim is to find out how the village head's roleis in improving public services in Inofina Village, North Moskona District, Teluk Bintuni Regency.The method used is a qualitative method with a descriptive study approach.The implementation ofPublic Services that has been happening all this time in Inofina Village, North Moskona District,Teluk Bintuni Regency is through a service procedure that is easy, fast and centered on the needsof the community; Settlement time is fast but some are slow due to inadequate funding andsupporting infrastructure; Implementation costs from village funds; Products or Service Resultscan be felt directly by the community through the ease of service; and Facilities and infrastructuresupporting the quality of public services need improvement and addition.Keywords: Public Services, The Role, Village Head.